Aplikasi Pengenalan Sejarah Indonesia berbasis Android - Anggi Dimas Prasetyo Hendar Linden; Redo Abeputra Sihombing; Heriyati Heriyati (Universitas Indraprasta PGRI Jakarta, 2020)
History lesson is generally only in the form of manual text accompanied by several images. It is as usually found in textbooks during school. Writing history is not far from rigid, flat and long writing, making history lesson less interesting to learn, with most school students considering it to be boring lesson. The purpose of this research is to change people's interest in studying history and to provide additional knowledge on how to make an application about introduction to Indonesian history. The application is useful for general public, especially for elementary school students to facilitate the process of learning Indonesian history. The research method used to design and create an introduction to Indonesian history is a grounded research method. After designing and making an application about introduction to Indonesian history, the researcher concludes that the application can provide solutions helping students to know the Indonesian history more easily. The created application help to make a learning method more effective and enjoyable.